PERNIKAHAN BEDA AGAMA MEBURUT ULAMA MADZHAB - Abdul Qadir Assagaf; Khoirul Asfiyak; Ibnu Jazari (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2022)
This study aims to find out how the law of interfaith marriage according to madzhab scholars. This study uses a type of qualitative research with an objective normative approach. Sources of data were obtained from books, books, laws and regulations and various literatures related to the legality of interfaith marriages according to Islamic law, namely the Qur'an and Hadith, as well as the opinions of Islamic scholars. Collecting data in the form of library research (library research). From this study, it was found that interfaith marriages are not valid according to the Hanafi, Maliki, Syafi'i, and Hambali madshab scholars, even the law which is the legal basis of the Indonesian state states interfaith marriages are not recognized and invalid.